Literature criticism from 1400 to 1800. Volume 2 - 4 0 16; Poupard, Dennis.;Ligotti, Thomas.;Scott, Mark W.; 5 (Detroit, Michigan : Gale Research Company, 1985)
Contains alphabetically arranged entries that profile thirteen world authors from the fifteenth through the eighteenth centuries, each with an introduction, a list of principal works, and a selection of critical excerpts.
LC 2--Cover.;Excerpts from criticism of the works of fifteenth, sixteenth, seventeenth, and eighteenth-century novelists, poets, playwrights, philosophers, and other creative writers, from the first published critical appraisals to current evaluations.
Includes bibliographical references and indexes.
Adult;Adult
Keywords: 2 -- 0; 6; History and criticism.;History and criticism. -- Criticism.;Literature, Modern;Criticism.;Literature; 20; 2